Associations of ATP-Sensitive Potassium Channel’s Gene Polymorphisms With Type 2 Diabetes and Related Cardiovascular Phenotypes - Liu, Cheng; Lai, Yanxian; Guan, Tianwang; Zhan, Junfang; Pei, Jingxian; Wu, Daihong; Ying, Songsong; Shen, Yan (Frontiers in Cardiovascular Medicine, 2022)
Type 2 diabetes (T2D) is characterized by increased levels of blood glucose but is increasingly recognized as a heterogeneous disease, especially its multiple discrete cardiovascular phenotypes. Genetic variations play key roles in the heterogeneity of diabetic cardiovascular phenotypes. This study investigates possible associations of ATP-sensitive potassium channel (KATP) variants with cardiovascular phenotypes among the Chinese patients with T2D. Six hundred thirty-six patients with T2D and 634 non-diabetic individuals were analyzed in the study. Nine KATP variants were determined by MassARRAY. The KATP rs2285676 (AA + GA, OR = 1.43, 95% CI: 1.13–1.81, P = 0.003), rs1799858 (CC, OR = 1.42, 95% CI: 1.12–1.78, P = 0.004), and rs141294036 (CC, OR = 1.45, 95% CI: 1.15–1.83, P = 0.002) are associated with increased T2D risk. A follow-up of at least 45.8-months (median) indicates further association between the 3 variants and risks of diabetic-related cardiovascular conditions. The associations are categorized as follows: new-onset/recurrent acute coronary syndrome (ACS) (rs2285676/AA + GA, HR = 1.37, 95% CI: 1.10–1.70, P = 0.005; rs141294036/TT + CT, HR = 1.59, 95% CI: 1.28–1.99, P < 0.001), new-onset stroke (rs1799858/CC, HR = 2.58, 95% CI: 1.22–5.43, P = 0.013; rs141294036/CC, HR = 2.30, 95% CI: 1.16–4.55, P = 0.017), new-onset of heart failure (HF) (rs1799858/TT + CT, HR = 2.78, 95% CI: 2.07–3.74, P < 0.001; rs141294036/TT + CT, HR = 1.45, 95% CI: 1.07–1.96, P = 0.015), and new-onset atrial fibrillation (AF) (rs1799858/TT + CT, HR = 2.05, 95% CI: 1.25–3.37, P = 0.004; rs141294036/CC, HR = 2.31, 95% CI: 1.40–3.82, P = 0.001). In particular, the CC genotype of rs1799858 (OR = 2.38, 95% CI: 1.11–5.10, P = 0.025) and rs141294036 (OR = 1.95, 95% CI: 1.04–3.66, P = 0.037) are only associated with the risk of ischemic stroke while its counterpart genotype (TT + CT) is associated with the risks of HF with preserved ejection fraction (HFpEF) (rs1799858, OR = 3.46, 95% CI: 2.31–5.18, P < 0.001) and HF with mildly reduced ejection fraction (HFmrEF) (rs141294036, OR = 2.74, 95% CI: 1.05–7.15, P = 0.039). Furthermore, the 3 variants are associated with increased risks of abnormal serum levels of triglyceride (TIRG) (≥ 1.70 mmol/L), low-density lipoprotein cholesterol (LDL-C) (≥ 1.40 mmol/L), apolipoprotein B (ApoB) (≥ 80 mg/dL), apolipoprotein A-I (ApoA-I) level (< 120 mg/dL), lipoprotein(a) Lp(a) (≥ 300 mg/dL) and high-sensitivity C-reactive protein (HsCRP) (≥ 3.0 mg/L) but exhibited heterogeneity (all P < 0.05). The KATP rs2285676, rs1799858, and rs141294036 are associated with increased risks of T2D and its related cardiovascular phenotypes (ACS, stroke, HF, and AF), but show heterogeneity. The 3 KATP variants may be promising markers for diabetic cardiovascular events favoring “genotype-phenotype” oriented prevention and treatment strategies.